Aging obviates sex‐specific physiological responses to exercise. Issue 2 (19th January 2013) - Deschenes, Michael R.; Taylor, Jessica L.; Mangis, Katherine A.
<x xml:space="preserve">Abstract</x> Objectives Both sex and aging have been shown to affect physiological responses to exercise. The aim of the present investigation was to determine whether aging impacted the sex‐specific nature of physiological responses to exercise commonly noted among young adults. Methods Ten aged men (69.0 ± 1.7 years; mean ± SE) and 10 aged women (71.6 ± 1.3 years) reporting similar levels of habitual physical activity performed a 30‐min exercise session at 60–65% of their predetermined peak oxygen uptake. Cardiovascular, thermoregulatory, and metabolic variables were assessed before exercise, at the 15th and 30th min of exercise, and at 5 and 15 min into a passive postexercise recovery period. Variables of interest were statistically analyzed via two‐way analysis of variance with repeated measures; significance was set at P < 0.05. Results Significant effects of time (i.e., exercise) for each physiological variable of interest were identified, but not once was a significant effect of group (i.e., sex) detected. Conclusions Exercise‐induced physiological responses to prolonged, moderate intensity exercise were similar among aged men and aged women. This evidence that the sexually dimorphic nature of physiological responses to exercise is obviated with age should be taken into account when prescribing health‐related exercise training programs for older individuals. Am. J. Hum. Biol. 25:215–221, 2013. © 2013 Wiley Periodicals, Inc.